Genome-Edited Plants and the Challenges of Regulating Their Biosafety in Indonesia - nFN Bahagiawati; Dani Satyawan; Tri J. Santoso (Jurnal AgroBiogen, 2019)
Genome editing is a precise breeding technique to improve plant properties by editing specific genes that regulate desired trait. Genome editing techniques can be designed so that the resulting plant does not contain foreign genes and the resulting changes in DNA sequences cannot be distinguished from products obtained by conventional gene mutations which have been considered as safe and therefore unregulated. Thus, genome editing products in some countries are also not specifically regulated as GM products even though their assembly process uses recombinant DNA and genetic transformation. Brazil, likeIndonesia ratified the Cartagena Protocol, but it issued a special  regulation that provides dispensation for several types of genome editing products and exempts them from regulations that apply to transgenic plants. The steps taken by other countries in regulating genome editing products can be taken into consideration in drafting regulations in Indonesia, in order to create a conducive environment that supports the use of this potential technology while at the same time provides assurance regarding its safety to human health and the environment. The purpose of this review was to provide information onthe development of genome editing technologies in plant breeding, analyze its risks compared to that of conventional breeding, and compare its biosafety regulation in various countries to provide some considerations for drafting regulations on the risk assessment of genome editing products in Indonesia, as a ratifying country of the Cartagena Protocol.